Observations of Co-Nest Building and Spawning in Native and Non-Native Chub Species (Nocomis spp.) in the Swannanoa River, North Carolina - Patrick Ciccotto (Southeastern Fishes Council Proceedings, 2024)
Co-nest building and spawning among individuals of the native population of River Chub (Nocomis micropogon) and among those of an introduced population of Bluehead Chub (N. leptocephalus) observed in the Swannanoa River (French Broad River basin) during Spring 2024 represents the first time such behaviors have been documented between two species of Nocomis. Observations of these behaviors are described and discussed in the context of potential hybridization and the impact of introduced Bluehead Chubs in the French Broad River basin.
Keywords: Species Introduction; Spawning Ecology; River Chub; Bluehead Chub